The Impact of Internal Audit, Internal Control and Whistleblowing System on Fraud Prevention in the Indonesia Banking Companies during the COVID-19 Pandemic - Kelvin Haryanto; Kenny Ardillah (Indonesia Banking School, 2021)
This study aims to analyze the factors that influence fraud prevention, which consists of the role of internal audit, internal control and the sistem whistleblowing. The population of this study are employees who work as internal auditor in the Indonesia banking companies. The number of samples selected through con-venience sampling method are 100 employees of the three private bank in Jakarta domiciled base that rep-resent Indonesia’s banking industry. The hypothesis in this study was tested using multiple linear regres-sion. The results of the study indicate that internal audit, internal control and the whistleblowing system have a significant positive effect on fraud prevention. Meanwhile, internal audit and internal control are the most dominant variables that affect fraud prevention. This result proved that for the companies, the best practices of implementing internal audit, internal control, and the whistleblowing system in the banking industry will further increase the efforts of fraud prevention in anticipating fraud practices by company’s employees.